The association among SES, screen time, and outdoor play in children at different ages: The GECKO Drenthe study - Lu, Congchao; Wiersma, Rikstje; Corpeleijn, Eva (Frontiers in Public Health, 2023)
Introduction This study examined the association among socioeconomic status (SES), screen time, and outdoor play in children at different ages in the GECKO Drenthe birth cohort study. Methods Valid data were obtained from two surveys at ages 3–4 years and 10–11 years. Screen time (TV watching and computer use) and outdoor play were reported by parents. Childhood SES was derived by a synthetic “Equivalized Household Income Indicator,” an estimated disposable income. Quantile regression models (cross-sectional analysis) and linear regression models (change between 3–4 and 10–11 years) were used. Results In general, screen time increased strongly from a median of 51 min/day at 3–4 years (n = 888) to 122 min/day at 10–11 years (n = 1023), whereas time spent on outdoor play remained stable over age (77 min/day at 3–4 years and 81 min/day at 10–11 years). More time spent on outdoor play (50th quantile) was found in children with low SES families at 3–4 years, while at 10–11 years, more outdoor play was found in the high SES group. At 10–11 years, in the higher ranges of screen time, children from high SES had relatively lower screen time [50th quantile: −10.7 (−20.8; −0.6); 75th quantile: −13.6 (−24.4; −2.8)]. In the longitudinal analysis (n = 536), high SES was associated with an increasing time spent on outdoor play [11.7 (2.7; 20.8)]. Conclusion Socioeconomic disparities in children's outdoor play and screen behavior may be more obvious with increasing age. Low SES may facilitate both outdoor play (at 3–4 years) and screen time (at 10–11 years); however, children from high SES families develop slightly more favorable behavior patterns with age.